MODEL WAKAF PRODUKTIF BERBASIS PESANTREN SEBAGAI INSTRUMEN PEMBANGUNAN EKONOMI UMAT - Wahyono, Catur (JSE: Jurnal Sharia Economica, 2025)
This study aims to analyze the empirical conditions of productive waqf management in pesantren and to formulate a productive waqf model based on Maqāṣid al-Sharī‘ah and sustainable development. The research employs a qualitative approach with a case study design and conceptual model development. Data were collected through in-depth interviews, observations, and document analysis, and were examined thematically by linking empirical findings with the Maqāṣid al-Sharī‘ah framework and sustainability principles. The findings reveal that pesantren possess significant waqf potential; however, its management remains predominantly consumptive, constrained by limited professional capacity of nazhir and weak institutional governance. This study proposes a productive waqf model that holistically integrates educational, economic, and social dimensions through strengthened governance, development of waqf-based productive business units, integration of Islamic social finance instruments, and the utilization of digital technology. The proposed model positions waqf as a strategic instrument for enhancing pesantren self-reliance and promoting sustainable socio-economic development of the Muslim community.